2022
DOI: 10.26773/smj.221006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Morphological Characteristics and Motoric Skills in Young Football Players’ Selection

Abstract: This research aims at showing the impact of basic morphological characteristics and specific motoric skills in the selection of young football players, specifically in showing the differences between FC Prishtina’s U17 first and second teams. 30 football players participated in this study and were divided into two teams: a first team (n=15) and a second team (n=15). The competitive season performance of football players served as the selection criterion. It was always based on the eye of the coaches. The morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Weight gain during participation in soccer is often associated with health risks (Churchill et al, 2018). Research conducted by (Sermaxhaj et al, 2022) revealed that soccer players were significantly influenced by motor skills (speed, agility, and endurance) but not by morphological characteristics (weight and height). According to research conducted by (Joksimović et al, 2019) revealed that morphological characteristics have a very vital role in determining the success of athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Weight gain during participation in soccer is often associated with health risks (Churchill et al, 2018). Research conducted by (Sermaxhaj et al, 2022) revealed that soccer players were significantly influenced by motor skills (speed, agility, and endurance) but not by morphological characteristics (weight and height). According to research conducted by (Joksimović et al, 2019) revealed that morphological characteristics have a very vital role in determining the success of athletes.…”
Section: Introductionmentioning
confidence: 99%